(3GdQSGdI GdCVMhjI aj CeQ GdeHOC hGdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CaGV Gddg Ydi QhM GdTjN GdGejf ai GdOGQjf hdfKHJ agQSJ GdaUhd GdehQOI ai gPg GdQSGdI eSJYjf HGddg hdi GdMQeI GdaUd GdChd ai eGFjI GdeYGO hGdaUd GdKGfi ai ENJdGa GdGQGA ajg s
(3BNQgG (B:s
(3EYOGe GdYOe hSHH GdGSHGH eG jSJMbgG HfaSgG ef GdHWdGf hcd TF gGdc EdG hLgI JeJ GdQSGdI GdaQOhS hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3gfGc NWC ai JQbje GdUaMGJ HYO UaMI (B224 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs